Effects of polyamines and polyamine biosynthetic inhibitors on mitotic activity of Allium cepa root tips - Ünal, Meral; Palavan Ünsal, Narçin; Tüfekçi, M. A. (AKADEMIAI KIADO, PRIELLE K U 19, H-1117 BUDAPEST, HUNGARY, 2008)
The genotoxic and cytotoxic effects of exogenous polyamines (PAs), putrescine ( Put), spermidine (Spd), spermine (Spm) and PA biosynthetic inhibitors, alpha-difluoromethylornithine ( DFMO), cyclohexilamine (CHA), methylglioxal bis-(guanylhydrazone) ( MGBG) were investigated in the root meristems of Allium cepa L. The reduction of mitotic index and the induction of chromosomal aberrations such as bridges, stickiness, c-mitotic anaphases, micronuclei, endoredupliction by PAs and PA biosynthetic inhibitors were observed and these were used as evidence of genotoxicity and cytotoxicity.
Keywords: allium cepa; chromosome aberration; mitotic activity; polyamine; polyamine biosynthetic inhibitor; cell-cycle; spermidine; growth; seedlings; plants; kromozom aberasyon; mitotik aktivite; poliamin; poliamin biyosentetik inhibitörü; hücre döngüsü; büyüme; fidan; bitkiler